Teknik Pembelajaran Talking Stick untuk Meningkatkan Aktivitas dan Hasil Belajar IPA - Nourina Kartika Sakti; Sihkabuden; Susilaningsih (Edcomtech: Jurnal Kajian Teknologi Pendidikan, 2016)
The purpose of this study is to describe the application of the talking stick technique, student activities, and student learning outcomes. The talking stick technique is a learning technique that is packaged in the form of a game using stick tools that aim to encourage students to have the courage to express their opinions. This study used a PTK design. The data was collected by means of observation, documentation and field notes. The results showed that the application of the talking stick technique could improve the activities and learning outcomes of science learning.